Kemampuan Komunikasi Matematis Siswa SMP melalui Model Quantum Learning - Lestari, Mulia; Darwani, Darwani; Yacoeb, M. (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2026)
This study aims to determine the comparison of the mathematical communication skill of students of class VIII SMP who are taught through the Quantum Learning model. Mathematical communication skills are still low due to the inability of students to channel their ideas systematically. The research method used was experimental research with a pretest-posttest control group design. The population in this study were all students of class VIII SMP Negeri 4 Langsa. Sampling was carried out using the Simple Random Sampling technique and obtained two classes, namely class VIII-5 as the experimental class and VIII-6 as the control class. Data collection was used by using a mathematical communication ability test sheet. From the research results obtained and , then means it can be concluded that the average mathematical communication skill of students who learned with Quantum Learning Model is better than the average mathematical communication skill of students who are taught using conventional learning.model. Mathematical communication skills are still low due to the inability of students to channel their ideas systematically. The research method used was experimental research with a pretest-posttest control group design. The population in this study were all students of class VIII SMP Negeri 4 Langsa. Sampling was carried out using the Simple Random Sampling technique and obtained two classes, namely class VIII-5 as the experimental class and VIII-6 as the control class. Data collection was used by using a mathematical communication ability test sheet. From the research results obtained and , then means it can be concluded that the average mathematical communication skill of students who learned with Quantum Learning Model is better than the average mathematical communication skill of students who are taught using conventional learning.